Video to Home Delivery of Evidence-Based Psychotherapy to Veterans With Posttraumatic Stress Disorder - Boykin, Derrecka M.; Keegan, Fallon; Thompson, Karin E.; Voelkel, Emily; Lindsay, Jan A.; Fletcher, Terri L. (Frontiers in Psychiatry, 2019)
Background: The Veterans Health Administration (VHA) has pioneered the implementation of video to home (VTH) technology to increase access to mental health treatments for Veterans facing barriers to receiving in-person care, particularly for posttraumatic stress disorder (PTSD). Randomized controlled trials have established the noninferiority of evidence-based psychotherapies (EBPs) for PTSD delivered through VTH, compared to in-person delivery. Less is known about the use of VTH to deliver EBPs for PTSD in routine clinical practice. Objective: We examined the provision of EBPs for PTSD delivered via VTH at a large Southwestern VHA PTSD outpatient clinic. Methods: Data were obtained from chart review of the electronic medical records of Veterans receiving at least one session of Cognitive Processing Therapy or Prolonged Exposure via VTH in the VHA PTSD clinic during the study time frame. Results: Fourteen providers (including six psychology trainees) delivered EBPs for PTSD via VTH between 2016-2018. Providers treated 74 Veterans (33.8% women) from diverse sociocultural backgrounds who ranged in age from 25 to 79. Most (83.8%) had never received psychotherapy in the VHA PTSD clinic. Each provider treated about 3.08 (± 2.18) Veterans using VTH, not including one provider who saw more than 30. A hybrid approach, in which VTH-delivery was coupled with in-person delivery, was used with 70.3% of Veterans across treatment (including sessions completed before initiation and after termination of the EBP). This demonstrates the versatility of VTH for meeting individual patient needs. Most EBP sessions (85.4%) were conducted over VTH. Despite Veterans attending an average of 6.85 (± 4.88) EBP sessions, 50% terminated before session 7. This dropout rate is consistent with national and local EBP completion averages within the VHA. Veterans receiving Cognitive Processing Therapy via VTH were more likely to complete treatment than those receiving Prolonged Exposure. No other patient factors predicted attrition. Conclusions: This study highlights the use of VTH as “tool in the toolbox” that expands the scope of practice for providers and increases opportunities for Veterans to receive EBPs for PTSD. We describe other potential advantages of using VTH to deliver EBPs for PTSD.